Synthesis of alkynylated benzo[a]naphtho[2,3-i]phenazine derivatives - Hahn, Sebastian; Biegger, Philipp; Bender, Markus; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2016)
Thermal condensation of 2,3-diamino-1,4-(bistriisopropylsilylethynyl)benzene, -naphthalene,-anthracene, and -benzothiadiazole substrates with 1,2-naphthalenedione forms bent benzophenazine-type heteroarenes in a one-step reaction in good to excellent yields. The targets are investigated by UV/Vis spectroscopy, cyclic voltammetry, and single-crystal X-ray crystallography. The packing of the targets in the solid state follows either a herringbone or a brick wall motif. In the case of 8,13-bis(triisopropylsilylethynyl)dibenzo[a,i]phenazine, polymorphs with either packing result.